Improved dielectric properties of Na1/2Y1/2Cu3Ti4O12 ceramics synthesized by ball-milling and reactive sintering - H Mahfoz Kotb; Mohamad M Ahmad; Adil Alshoaibi; Hassan A Khater; Abdullah Aljaafari (Materials Research Express, 2020)
Na _1/2 Y _1/2 Cu _3 Ti _4 O _12 (NYCTO) ceramics with giant dielectric constant ( ε ′) were synthesized by simple reactive sintering. NYCTO nanopowder was first synthesized using high energy ball-mill. Then the pelletized powder was sintered in air at temperatures in the range 975 °C to 1050 °C for 10–20 h. The obtained ceramics showed pure CaCu _3 Ti _4 O _12 (CCTO)-like cubic phase as revealed by x-ray diffraction measurements. Field effect-SEM observations showed that the grain size increases from 2 μ m to 5 μ m with increasing sintering temperature. NYCTO samples sintered at temperatures higher than 975 °C showed giant dielectric constant (10 ^3 –10 ^4 ) over most of the frequency range. The minimum dielectric loss (tan δ ) of ∼0.055 at 300 K has been approved for the ceramic sample sintered at 1050 °C. Impedance and modulus spectra of the current samples showed two relaxations related to semiconductor (grain) and high resistance (grain-boundaries) elements. The activation energy for conduction located in the range 0.1–0.5 eV highlighted the role of single ionized oxygen vacancies in the dielectric properties of the investigated NYCTO ceramics.